Macrophage Metabolism As Therapeutic Target for Cancer, Atherosclerosis, and Obesity - Geeraerts, Xenia; Bolli, Evangelia; Fendt, Sarah-Maria; Van Ginderachter, Jo A. (Frontiers in Immunology, 2017)
Macrophages are essential components of innate immunity that contribute to host defense against infections, but also tumor growth and the maintenance of tissue homeostasis. An important feature of macrophages is their plasticity and ability to adopt diverse activation states in response to their microenvironment and in line with their functional requirements. Recent immunometabolism studies have shown that alterations in the metabolic profile of macrophages shape their activation state and function. For instance, to fulfill their respective functions LPS-induced pro-inflammatory macrophages and IL-4 activated anti-inflammatory macrophages adopt a different metabolism. Thus, metabolic reprogramming of macrophages could become a therapeutic approach to treat diseases that have a high macrophage involvement, such as cancer. In the first part of this review we will focus on the metabolic pathways altered in differentially activated macrophages and link their metabolic aspects to their pro- and anti-inflammatory phenotype. In the second part we will discuss how macrophage metabolism is a promising target for therapeutic intervention in inflammatory diseases and cancer.